Aplikasi Sistem Informasi Geografis dan Penginderaan Jauh Untuk Analisis Potensi dan Kerentanan Longsor di Kecamatan Kintamani, Bangli - Ardana, Made Putra Eka; Diara, I Wayan; Narka, I Wayan (Fakultas Pertanian Universitas Udayana, 2024)
Application of Geographic Information System and Remote Sensing for the Analysis of Landslide Potention and Vulnerability in Kintamani District, Bangli Regency. Kintamani District is an area that is prone to disasters; this is because of its geographical conditions which are located in the highlands and mountains with steep slopes. Research in this area is important to provide information on landslides for the public and government. The objective of this research is to determine the potential and landslide vulnerability. Delineating the potential for landslides used integration of remote sensing data and Geographic Information System (GIS) through the scoring method by overlaying the thematic that causes landslides (zones of susceptibility to soil movement, rainfall, land use, slope and soil type). The determination of landslide vulnerability is carried out by overlaying the landslide potential map with the settlement and road map. The results showed that Kintamani District has four landslide potential classes, namely the non-potential class which is a water area (Batur Lake) covering an area of 1616.13 ha, a low potential of 9350.61 ha, a medium potential of 15021.89 ha and a high potential of 10558.62 ha. The level of vulnerability to landslides in settlements consists of three classes, namely a low vulnerability class covering 1041.49 ha, a medium vulnerability area of 811.36 ha and a high vulnerability area of 174.52 ha. The level of vulnerability to landslides on the 307.16 km road network consists of two types of roads, namely primary collector roads and local roads. There are 23 distribution points of landslides found in research locations spread across Belancan, Kintamani, Bantang, Dausa, Sukawana, South Batur, Central Batur, Abangsongan, Abang Batudinding, and Trunyan Villages.